Immune checkpoint blockade can synergize with radiation therapy, even in tumors resistant to checkpoint monotherapy - Dörrie, Jan (Embo Molecular Medicine, 2017)
Immunotherapy has evolved as a new pillar of cancer treatment during the last decade. The main breakthrough was the development of immune checkpoint blocking (ICB) antibodies, which antagonize inhibitory receptors on T cells and their ligands and thus unleash the cellular immune system against the tumor. ICB showed tremendous effects in several types of cancer. However, only a proportion of the patients suffering from tumors, which are in principle sensitive, benefit from this treatment and other kinds of neoplasia are completely resistant. Great effort is currently being undertaken to distinguish responders from non-responders, and concepts to turn the latter into the former are urgently required. One approach is to combine ICB with already well-established treatment strategies, that is, the other mainstays of cancer therapy such as surgery, radiation therapy (RT), and chemotherapy. Depending on the circumstances, both chemotherapy and RT may act either immune suppressively or immune stimulatingly. In this issue of EMBO Molecular Medicine, Azad etal () show that indeed, pancreatic ductal adenocarcinoma, which is resistant to ICB monotherapy, becomes responsive to this treatment by simultaneous RT or chemotherapy.
EVALuna2:35414